Efeito do tratamento periodontal em pacientes com Diabetes Mellitus Tipo 2 moderadamente compensados e descompensados - Bernardon, Paula (2015)
Aim: Recent studies demonstrate Diabetes Mellitus (DM) as a risk factor for the impairment of periodontal health and a growing body of evidence has been supporting periodontal disease (PD) as having an adverse effect on glycemic control and on the pathophysiology of the diabetes-related complications. This study aims to evaluate the effect of periodontal therapy immoderately compensated and decompensated type 2 diabetic patients. Subjects and methods: 40 patients with DM2 and periodontal disease were selected and divided into two groups: Group 1: Moderately compensated; Group 2: Decompensated. Of these 40 patients, only 35 participated in the study. The analyses were performed at 0, 3 and 6 months after scaling and root planning and including clinical periodontal parameters and the quantification of gingival crevicular fluid (GCF). Glycated hemoglobin (HbA1c), fasting glucose (FG) and IL1-β expression were measured. Results: Both groups presented improvement in all clinical periodontal parameters as well as quantification of gingival crevicular fluid and in the expression of IL-1ß present in the fluid after 6 months. However, no statistically significant difference was found in the levels of HbA1C in the first group after 6 months, although a significant increase was found after six months in the other group. While in relation to the FG, a great improvement was found in the first group and a significant increase in the second group after six months. Conclusion: It was possible to observe that conventional periodontal treatment (scaling and root planing) is more effective for moderately compensated type 2 diabetic patients glycemic control rather than for the decompensated patients.